The role of testosterone and cortisol levels in nonsuicidal selfinjury in adolescents - Calvete, Esther; Faura-García, Juan; Orue, Izaskun; Prieto-Fidalgo, Ángel (Journal of Adolescence, 2025)
Introduction Nonsuicidal selfinjury (NSSI) is an important problem in adolescence, which is thought to serve several reinforcement functions (positive vs. negative, automatic vs. social). While the psychological mechanisms involved in NSSI are relatively well known, there is an important gap in the knowledge regarding the underlying biological mechanisms. This study examined the role of testosterone (T) and cortisol (C) in the frequency and reinforcement functions of NSSI. Methods A total of 423 adolescents (age range = 13–17; 54.4% girls) from Basque Country (Spain) provided saliva samples to determine T and C levels and completed measures of NSSI 6 months later in 2017–2018. Results The results showed that T but not C was significantly associated with higher NSSI frequency and the four types of NSSI functions. In addition, C moderated the predictive association between T and NSSI for automatic negative reinforcement, such that this association was significant only when C was high. Participant sex did not moderate any association between hormones and NSSI. Conclusions These preliminary results suggest that testosterone levels can affect NSSI behaviors in adolescence, thus helping to explain the increase in NSSI during this stage. Moreover, in situations in which NSSI serves to alleviate negative internal states, high levels of cortisol can be involved.
Keywords: adolescence; nonsuicidal selfinjury; testosterone; cortisol